MORBIDITY WITH TEMPORAL DISABILITY AMONG DRIVERS OF PASSENGER VEHICLES IN METROPOLIS CONDITIONS - B.KH. NUSHERVONI; A.B. BABAEV; F.D. KHASANOV; L.E. ODINAEVA (Avicenna Tajik State Medical University, 2020)
Objective: To study of morbidity with temporal disability (MTD) among drivers of passenger vehicles in metropolis conditions. Methods: Analysis of the MTD among drivers of passenger vehicles in metropolis conditions has been carried out in 2016-2018. According to the character of their work, drivers were divided into two professional groups: drivers of buses of the AKIA, ISUZU, LiAZ brand and TIU brand trolleybuses. In total, 224 sick lists were taken for analysis: from them, 128 were bus drivers and 96 trolleybus drivers. Results: The general MTD analysis showed that the number of diseases of bus drivers averaged 99.5, and days of disability 1891.2; the same numbers were in trolleybus drivers - 60.0, and 996.0 respectively. And that, the average duration of one morbidity case for bus drivers was 14.8 days, and for trolleybus drivers 10.4 days. An analysis of morbidity structure shows that the most frequently observed cases were diseases of the respiratory, digestion, musculoskeletal, cardiovascular and central nervous systems, which is caused by exposure to unfavorable factors of the industrial environment. The highest rates of MTD were mostly observed at the age groups of 50-59 years and older. With the increase in the experience of bus and trolleybuses drivers, the incidence of morbidity rates increased, especially among trained workers. Conclusion: Thus, drivers of passenger vehicles are affected by adverse factors in the working environment, which is the main cause of morbidity with temporary disability. The incidence rate is significant among age group drivers of 50-59 years and older, and also drivers with work experience of 17 years or more.